Strategies for Minimizing Corruption in the Construction Industry in China - X.W, Patrick . Zou (Penerbit Universiti Sains Malaysia, 2006)
Corruption is a social phenomenon deep rooted in the history of mankind. It is similar to other kinds of crime which are likely to occur in procurement of works by governments and local authorities, due to the large amount of money involved in a single transaction and the difficulty in monitoring project expenditure. Therefore, it is necessary to develop strategies to minimize any corruption risks and corrupt behaviour in procurement of construction projects. The aim of this paper is to review the current corruption prevention practices in China’s construction industry and suggest ways for improvement. To collect useful and insightful information, desktop studies, focus-group workshops and face-to-face interviews were conducted with supervisory and construction officers at different levels – state, province and municipal in China, who have direct responsibilities and experience in cracking down construction corruption. It was found that corruption happens in different forms during any stage of construction project procurement, and the current anti-corrupt practices are reactive rather than proactive. It was also found that improvements on the legal system, inspection strategies and processes, and promotion of ethical culture are all required. Based on the research findings, corruption prevention strategies were developed. The paper concludes that institution of random and regular checks, severe punishment and prosecution to corrupt personnel, and promotion of a healthy and clean construction culture are all necessary to mitigate the scourge.